Triboelectric Nanogenerators: Nonpolar Liquid Lubricant Submerged Triboelectric Nanogenerator for Current Amplification via Direct Electron Flow (Adv. Energy Mater. 25/2021). Issue 25 (8th July 2021) - Chung, Seh‐Hoon; Chung, Jihoon; Song, Myunghwan; Kim, Seonwoo; Shin, Dongjun; Lin, Zong‐Hong; Koo, Bonwook; Kim, Dongseob; Hong, Jinkee; Lee, Sangmin
Abstract : In article number 2100936, Dongseob Kim, Jinkee Hong, Sangmin Lee and co‐workers report a non‐polar liquid lubricant submerged triboelectric nanogenerator which can generate high output and charge commercial batteries by effectively suppressing air breakdown due to the large Debye length of the liquid lubricant. In addition, it is able to reduce friction wear by the lubrication and rolling friction.